2011
DOI: 10.3727/096368911x565038
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Sinoatrial Node Cells Into Canine Right Ventricle: Biological Pacing Appears Limited by the Substrate

Abstract: Biological pacing has been proposed as a physiologic counterpart to electronic pacing, and the sinoatrial node (SAN) is the general standard for biological pacemakers. We tested the expression of SAN pacemaker cell activity when implanted autologously in the right ventricle (RV). We induced complete heart block and implanted electronic pacemakers in the RV of adult mongrel dogs. Autologous SAN cells isolated enzymatically were studied by patch clamp to confirm SAN identity. SAN cells (400,000) were injected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 68 publications
6
54
1
Order By: Relevance
“…In an animal model of ALI, Yamada et al [24] have shown that administration of LPS to murine lungs induced rapid release of EPCs into the circulation, which contributed to lung repair after LPS-induced lung injury in mice. Furthermore, transplantation of circulating EPCs or mesenchymal stem cells attenuated ALI induced by oleic acid, hyperoxia and Escherichia coli or pancreatitis-associated lung injury [25,26,27,28,29,30], and improved survival in rats with LPS-induced lung injury [31]. These studies suggest that EPCs are important for lung repair in lung injury.…”
Section: Discussionmentioning
confidence: 93%
“…In an animal model of ALI, Yamada et al [24] have shown that administration of LPS to murine lungs induced rapid release of EPCs into the circulation, which contributed to lung repair after LPS-induced lung injury in mice. Furthermore, transplantation of circulating EPCs or mesenchymal stem cells attenuated ALI induced by oleic acid, hyperoxia and Escherichia coli or pancreatitis-associated lung injury [25,26,27,28,29,30], and improved survival in rats with LPS-induced lung injury [31]. These studies suggest that EPCs are important for lung repair in lung injury.…”
Section: Discussionmentioning
confidence: 93%
“…Similar to the therapeutic benefit reported for bone marrow-derived MSCs, studies utilizing UCB-derived MSCs report comparable effects in the hyperoxia-induced model of neonatal lung injury [29,31,32,33,36] - improved alveolar structure/restoration of alveolar growth, attenuation of lung fibrosis, reduced lung inflammation, prevention of impaired lung angiogenesis, and improved exercise capacity. Furthermore, the beneficial long-term effects of UCB-derived MSC administration were also demonstrated, with no evidence of adverse effects in adulthood [29,36].…”
Section: The Basis For Using Stem Cells To Treat Bpdmentioning
confidence: 66%
“…Furthermore, the beneficial long-term effects of UCB-derived MSC administration were also demonstrated, with no evidence of adverse effects in adulthood [29,36]. Studies utilizing UCB-derived MSCs have also assessed the differences between the route of administration [31], dose of MSCs [32] and timing of the dose [33], with more favorable outcomes occurring with intratracheal administration with a minimum of 5 × 10 4 MSCs and optimal protective effects with 5 × 10 5 MSCs. Furthermore, administration in the early stages of lung development (prealveolar stage) was more beneficial than in the later stages (postalveolar stage).…”
Section: The Basis For Using Stem Cells To Treat Bpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the lack of such power-law behavior should not necessarily exclude candidate cell types. Recent work by Zhang et al 12 demonstrated that even when a large number of SAN cells are autologously transplanted to the right ventricle of canine hearts, the range and success of pacemaking activity of the SAN cells are limited in the ventricle compared with their normal atrial environment. This underscores the importance of the host environment in influencing the resultant pacemaker activity and is likely attributable to the local anatomy, cell-cell coupling, and source-sink interactions, meaning that the resulting pacemaking activity is highly dependent on the amount of depolarizing current produced by the pacemaker cells relative to the amount of this current absorbed by the surrounding ventricular myocardium.…”
Section: Article See P 883mentioning
confidence: 99%